Investigation of wind effect at Samsun, Zonguldak, and Trabzon airports in Turkiye - Uzun, Omer Faruk; Hosbas, Ramazan Gursel (HUNGARIAN METEOROLOGICAL SERVICE, 2026)
management of weather conditions plays a critical role in ensuring safe and efficient flight operations in the aviation industry. In this context, the wind factor has a direct impact on aircraft performance and pilot decision-making mechanisms, especially during landing and takeoff processes. Within the scope of the study, 16 years of wind data recorded between 2008 and 2023 at Samsun & Ccedil;ar & uacute;amba, Zonguldak, and Trabzon airports located in the Black Sea Region are analyzed. Innovative Trend Analysis (ITA) and Innovative Polygon Trend Analysis (IPTA) methods are used to analyze the trends of wind direction, speed, and sudden changes. According to the results obtained, the dominant wind direction at Samsun & Ccedil;ar & uacute;amba and Zonguldak airports was determined as east (E), while a dominant wind effect was determined in the south-southwest (SSW) direction at Trabzon Airport. The study reveals the effects of wind factor on flight safety and operational efficiency and provides recommendations for the measures to be taken in the aviation sector and future practices.
Keywords: flight safety; airport operations; crosswind and tailwind; trend analysis; wind factor; AIRCRAFT; Meteorology & Atmospheric Sciences